Stress-induced reinstatement of amphetamine-conditioned place preference and changes in tyrosine hydroxylase in the nucleus accumbens in adolescent rats - Cruz, Fabio C. [UNESP]; Leao, Rodrigo M. [UNESP]; Marin, Marcelo Tadeu [UNESP]; Planeta, Cleopatra da Silva [UNESP] (Pergamon-Elsevier B.V. Ltd, 2010)
Drug abuse among humans often begins during adolescence. Exposure to psychostimulants during this age period may have long-term consequences which can render the organism more susceptible to drug abuse and relapse later in life. It has been demonstrated that exposure to stress can promote relapse to drug use even after long periods of withdrawal. The reinstatement of conditioned place preference (CPP) is a useful animal model for studying relapse. In humans and animals, changes in tyrosine hydroxylase (TN) have been related to drug addiction. Our study examined whether amphetamine-induced CPP during adolescence could be reinstated by exposure to stress 1 (adolescence) and 30 (adulthood) days after the extinction test. We also investigated TH levels following the reinstatement of CPP. Our results showed that amphetamine-induced CPP during adolescence can be reinstated by stress exposure 1 day (P42, end of adolescence) but not 30 days after extinction (P71, adulthood). Moreover the reinstatement of AMPH-induced CPP by stress exposure occurred in the presence of decreased TH in the nucleus accumbens. In conclusion, our data add new evidence that neuroadaptations on TH may mediate relapse to drug-seeking behavior induced by stress within adolescence. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Amphetamine; Stress; Conditioned place preference; Reinstatement; Adolescence; Rat